Facilities and Infrastructure Management in Improving Student Non-Academic Field Achievement - Nur Annita Rahmawati; Nurul Latifatul Inayati (JIE (Journal of Islamic Education), 2024)
This research aims to discuss managing facilities and infrastructure to improve students' non-academic achievements. This research uses a type of field research with a phenomenological approach. Data collection techniques are done through observation, interviews, and documentation. Data reduction, data presentation, and conclusion are the data analysis techniques used. Testing the validity of the data is a triangulation of sources, methods and time. The results of this research show that the implementation of facilities and infrastructure management is carried out at the planning stage through meetings with the principal and deputy principal for the facilities and infrastructure section as well as all assistant principals, the procurement stage through providing facilities for organizational spaces and extracurricular spaces with student operational assistance funds and contribution to educational development, use step through implementing rules and making schedules for facility use, storage stage by storing facilities in a particular place with a separate person in charge, inventory stage through coding and recording assets in the Muhammadiyah Asset Management Information System, maintenance stage through two types, namely daily maintenance and periodic maintenance, elimination stage by removing damaged facilities. To improve students' non-academic achievements, all school parties, especially the facilities and infrastructure department, are renewing and providing the best non-academic infrastructure for students to gain enthusiasm and comfort in achieving.